E Estimasi Nilai Ekonomi Obat Bebas Tidak Digunakan Pada Kalangan Rumah Tangga Kecamatan Banjarmasin Timur - Muhammad Naufal; Melviani Melviani; Muhammad Riduansyah (Jurnal Pelayanan Kefarmasian dan Sains, 2021)
Background: The total cost of health care is most influenced by spending on drugs and is estimated to have financial consequences. The cost of unused drugs in Indonesia is still less of a concern and the basis for evaluating the loss of health care costs incurred by patients or the community. Objective: To determine the estimated economic value of over-the-counter drugs that are notused among households in EastBanjarmasin District. Methods: The research used is a survey type with information collection using a questionnaire. The population and sample are the people of East Banjarmasin District with a total of 100 respondents, takenusing probability sampling technique. The data were analyzed using Microsoft Excel, the estimated cost was calculated based on the Highest Retail Price listed on private pharmacy online services in Rupiah (Rp) and percentage (%). Results: This study founddrugs that were being used and as supplies, namely Rp.411,278 (58%) of the total price of drugs with an average per person of Rp.3.917, with the status of drugs that were no longer used in the people of East Banjarmasin District who the cost calculationhas been carried out and the cost is Rp. 224,317 (32%) with an average per person of Rp. 3,348, and for expired drugs, the cost is Rp. 72,660 (10%) with an average of Rp. 2,270 per person. Conclusion: The number of households storing leftover drugs multiplied by the average price of unused drugs per person in the household is Rp. 3,348 in this study, the economic value of unused drugs that can be saved is Rp. 163,429,272.Keywords:Economic Value, OTC Drugs, Household